THE IMPACT OF TAX AWARENESS, TAX SANCTIONS, AND TAX KNOWLEDGE ON INDIVIDUAL TAXPAYER COMPLIANCE - Kania, Niken Yofi; Priono, Hero (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
The intent of this study is to examine the variables which would impress individual taxpayer compliance in Nganjuk Regency by using independent variables which include tax knowledge, tax awareness, and tax sanctions. Analyzing primary data collected by distributing questionnaires to 100 eligible respondents using a quantitative approach. SPSS 26 is used in the analysis to do multiple linear regression. The study's findings indicate that tax awareness and knowledge have a significant impact on individual taxpayer compliance. However, tax sanctions have little effect on individual taxpayer compliance. Indirectly, this research proves that tax sanctions do not influence taxpayer compliance in Nganjuk Regency, and its results or level of influence differ from other studies that focused on areas outside Nganjuk Regency. This study will demonstrate whether awareness, sanctions, and knowledge are among the factors influencing taxpayer compliance in Nganjuk Regency. Individual taxpayer compliance is influenced by tax knowledge and awareness, but it is unaffected by tax sanctions. Of the three hypotheses formulated, it's evident that only the first and third hypotheses are accepted, whereas the second hypothesis is rejected.